Pengaruh Kedisiplinan dan Motivasi Terhadap Kinerja Karyawan Pada PT. Jawa Berkat Utama - Anjas Asmara; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe importance of discipline and employee motivation to improve employee performance is that by increasing discipline and work motivation, it is expected that production can run smoothly and labor productivity can be increased, so that production targets can be achieved and ultimately company goals can also be achievedit is expected that the workforce feels satisfied, because the work of the workforce is truly valued with rewards that are in accordance with the results obtained, so that the employee besides getting material and satisfaction in return for his salary, will also get psychological satisfaction, because it has received flattery or appreciation. To find out and analyze the effect of partially disciplined variables and work motivation affect the performance of employees at PT. Jawa Berkat Utama.Based on the results of the study note that variable work motivation and work discipline significantly influence the performance of employees of PT. Jawa Berkat Utama. Keywords: Discipline, Motivation and Employee Performance